Multiethnic Malaysia: Past, Present and Future edited by Lim Teck Ghee, Alberto Gomes and Azly Rahman, Petaling Jaya: Strategic Information and Research Development Centre (SIRD) and Malaysia Institute of Development and Asian Studies (MiDAS), 2009, 530 p - Mustafa Kamal Anuar , (Kajian Malaysia, 2010)
Aimed at producing a ''counter-hegemonic'', or alternative, corpus of writing ''that can provide different insights and perspectives on the country's history and development'' compared to the official or government-sanctioned literature on Malaysian history and society, Multiethnic Malaysia: Past, present and future is indeed a volume that makes a compelling read not only for university students but also other interested and concerned Malaysians and scholars as well.